Standardized Reporting of HCC with LI-RADS and mRECIST: Update on the Situation in Germany - Nelles, Christian; Ristow, Inka; Juchems, Markus S; Wessling, Johannes; Ringe, Kristina Imeen; Fehrmann-Efferoth, Ana; Lennartz, Simon; Afat, Saif; Othman, Ahmed; Eisenblätter, Michel; Paul, Roman; Gerwing, Mirjam; Persigehl, Thorsten (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
Online survey about the current status of CT protocols in hepatocellular carcinoma (HCC) in the year 2023/2024. Moreover, the usage of structured reporting using LI-RADS and mRECIST was surveyed and the results were compared with a survey from 2020.Radiologists working in outpatient or inpatient care in Germany were invited. The survey was conducted between 10/2022 and 06/2023 and between 06/2024 and 08/2024. HCC-related questions were asked regarding the commonly used imaging modalities, body coverage, and contrast phases in CT, as well as the usage of structured assessment and treatment response using mRECIST and LI-RADS.More than half of the participants stated that they “frequently” perform imaging of HCC. In the CT protocol, acquisition of a pre-contrast phase was widespread. While a late arterial and a portal venous contrast phase was acquired in most cases, a delayed phase was used much less frequently (at small and medium-sized hospitals only in 26.5%). For staging, LI-RADS was used in structured reports in only 13%; for response monitoring mRECIST was used at university hospitals in only 26.5% and LI-RADS in 14.7%, whereas these have been almost never used in routine practice at all other sites. The main reasons given for the lack of application were the expenditure of time, the lack of reporting templates, problems with integration into the IT infrastructure and a lack of reimbursement.The recommendation of a three phase CT examination in late arterial, portal venous, and delayed phase for HCC diagnostics according to LI-RADS is only partially implemented in Germany. Structured reporting for staging and response monitoring using LI-RADS and mRECIST was at a similarly low level in Germany in 2023 compared to 2020. Possible solutions include the development and distribution of online educational resources, structured reporting templates, and inexpensive IT solutions.Online-Umfrage zur aktuellen Statuserhebung von CT-Protokollen zur Diagnostik des hepatozellulären Karzinoms (HCC) im Jahr 2023/2024. Darüber hinaus wurde das Nutzungsverhalten strukturierter Befundung mittels LI-RADS und mRECIST erfragt und wurden die Ergebnisse mit einer Umfrage aus 2020 verglichen.Die Zielgruppe der Umfrage waren alle in der ambulanten oder stationären Versorgung tätigen Radiologinnen und Radiologen in Deutschland. Die Umfrage erfolgte im Zeitraum 10/2022 bis 06/2023 und 06/2024 bis 08/2024. Hierbei wurden HCC-bezogene Fragen gestellt hinsichtlich der üblich eingesetzten Bildgebungsmodalitäten, zur Körperabdeckung und zu den Kontrastmittelphasen in der CT sowie zum Nutzungsverhalten von strukturierter Beurteilung und des Therapieansprechens mittels mRECIST und LI-RADS.Mehr als die Hälfte der Teilnehmer gab an, eine Ausbreitungsdiagnostik des HCC „häufig“ durchzuführen. Im CT-Protokoll war die Akquisition einer nativen Phase weit verbreitet. Während die spätarterielle und portalvenöse Kontrastmittelphase in den meisten Fällen akquiriert wird, wird eine Spätphase deutlich seltener genutzt; an kleinen und mittelgroßen Krankenhäusern nur in 26,5%. Beim Staging wurde nur in 13% der Fälle immer strukturiert LI-RADS angewandt; für die Beurteilung des Therapieansprechens wurde an Universitätskliniken nur in 26,5% mRECIST und in 14,7 % LI-RADS verwendet, während diese in allen anderen Tätigkeitsstätten nahezu nicht in der Routine angewandt werden. Als Gründe für die fehlende Anwendung wurden vorwiegend der Zeitaufwand, fehlende Befundvorlagen, Probleme bei der Integration in die IT-Infrastruktur und eine fehlende Vergütung genannt.Die Empfehlung einer dreiphasigen CT-Untersuchung in spätarterieller, portalvenöser und Spätphase zur HCC-Diagnostik gemäß LI-RADS wird in Deutschland nur teilweise umgesetzt. Die strukturierte Befundung beim Staging und Responsemonitoring mittels LI-RADS und mRECIST lag 2023/2024 im Vergleich zu 2020 auf einem ähnlich niedrigen Niveau. Mögliche Verbesserungsansätze sind die Entwicklung und Verbreitung digitaler Weiterbildungsinhalte, deutschsprachiger Befundungsvorlagen und preiswerter IT-Lösungen.
Keywords: staging; Liver Imaging Reporting and Data System (LI-RADS); hepatocellular carcinoma (HCC); modified RECIST (mRECIST)